Preferential S/Se occupation in an anisotropic ReS2(1−x)Se2x monolayer alloy - Yuzheng Guo (Nanoscale, 2017)
Band structure engineering of two-dimensional (2D) metal dichalcogenides (TMDs) is crucial for their light–matter interaction and optoelectronic applications. Alloying of different metal or chalcogen elements with different stoichiometries in TMDs provides a versatile and efficient approach for modulating the electronic structure and properties of 2D materials. In 2D alloys, quantification of spatial distribution and local coordination of atoms facilitates the establishment of the structure–property relationship at the atomic scale. Here, we have imaged and analyzed the atomic configuration of sulfur and selenium atoms in anisotropic ReS1.4Se0.6 by scanning transmission electron microscopy (STEM). In Z-contrast images, we have realized the identification and quantification of Re, Se and S at different coordination sites. Different from the random distribution of metal and chalcogen elements in MoS2(1−x)Se2x and Mo1−xWxS2, we find that Se atoms preferentially locate inside of Re4 diamonds in ReS2(1−x)Se2x. Further density function theory (DFT) calculations reveal electronic structure modulation for Se occupation at different sites.